Selection of dust cleaning equipment such as cyclone for metalworking industries using the Hierarchy Analysis Method - V. Yu. Solomin; S. V. Belkova; V. Yu. Solomin (Омский научный вестник)
Metalworking is the main industrial production and its technological process requires dust cleaning. The choice of dust-collecting units from a trivial approach turns into a compact-multi-criteria one and requires the study of methods for its implementation. This article uses the method of selection of dust-cleaning equipment of cyclone type based on dust from metalworking industries based on the Hierarchy Analysis Method.